2021
DOI: 10.1111/are.15597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation time with Schizochytrium microalgae meal on growth, meat quality and fatty acid composition of Nile tilapia

Abstract: Five hundred Nile tilapia were fed with two diets (with or without microalgae Schizochytrium sp. meal) for different periods (0, 15, 30, 45 and 60 days). The aim of the present study was to investigate the effects of the time of supply of Schizochytrium sp microalgae meat in the diet on growth, fatty acid profile and meat quality of Nile tilapia. At growth performance, only the feed consumption and the final weight of the animals varied quadratically, reducing the estimated period to 37 and 38 days respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In the study of Nile tilapia, the deposition level of muscle DHA was in line with the dietary Schizochytrium sp. (rich in DHA) level [ 30 ]. Additionally, with the increase of muscular n-3 LC-PUFA content, the nutritional indices of FAs were significantly modified in the common carp treated with diets D2 and D3, such as n-6/n-3 PUFA, FLQ, and IT.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Nile tilapia, the deposition level of muscle DHA was in line with the dietary Schizochytrium sp. (rich in DHA) level [ 30 ]. Additionally, with the increase of muscular n-3 LC-PUFA content, the nutritional indices of FAs were significantly modified in the common carp treated with diets D2 and D3, such as n-6/n-3 PUFA, FLQ, and IT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that fishes generally have a specific thermal range in which they show a rapid increase in growth rate as temperature rises, with a significant decreasing rate as temperature exceeds the optimum temperature (Diamond et al, 2017; Imsland et al, 1996). On the other hand, temperature can indirectly affect fish growth by controlling consumption and conversion of feed (Jorge et al, 2021; Rogacki et al, 2019). Thus, the establishment of optimum temperature for growth is crucial to accelerate production efficiency of A. fasciatus .…”
Section: Introductionmentioning
confidence: 99%